Tahlil 'Anashir Al-Tarjamah - Azwir Azwir (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
The most crucial fundamental Arabic linguistic elements to master are Nahu, Sharf, and Dilalah. This is crucial for the development of a decent phrase when translating Indonesian text into Arabic. This research objective is to investigate how Arabic Language Education students employ Nahu, Sharf, and Dilalah when translating Indonesian literature into Arabic. To identify useful phrases, the research model takes the form of a content study of the structure of Nahu, Sharf, and Dilalah. This study revealed that the student's capacity to apply Nahu, Sharf, and Dilalah was seriously lacking. This is evidenced by their interactions with literature that cannot be translated into plain Arabic.